Model Komunikasi Media Alternatif untuk Pemberdayaan Perempuan Pascatambang Timah Bangka Belitung - Joko Mohamat Santoso; Achmad Riyadi (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study aims to formulate a women’s empowerment communication model in post-tin-mining environmental governance in Bangka Belitung, Indonesia. Women affected by ecological degradation caused by mining experience multiple vulnerabilities, including loss of economic access, increasing domestic burdens, and marginalization in environmental decision-making processes. This research employed a qualitative case study approach through in-depth interviews, field observations, and focus group discussions involving women tin panners, academics, environmental activists, and policymakers. Data were analyzed using grounded theory-based coding techniques, data reduction, and triangulation. The findings reveal that women’s voices remain confined to private and informal community spaces due to patriarchal pressures and economic dependence on mining activities. The study identifies five main components of the women’s empowerment communication model: community dialogue as a space for critical consciousness, community-based alternative media as an advocacy channel, gender-based digital literacy to strengthen communication capacity, data-based knowledge as a source of environmental advocacy legitimacy, and policy access through participatory village forums and regional planning mechanisms. The model demonstrates that communication functions as a strategic instrument to transform women from passive victims into active subjects in inclusive, gender-just, and sustainable environmental governance.